How much you felt or how you perceived? A study of emotional intensity and perceptual framing on false memory susceptibility. - Ng, Joycelin Pei Li. (2011)
The current study investigated the effect of different encoding contexts (emotional or perceptual framing) on susceptibility to false memory through imaginal elaboration, and the effect of emotional intensity on false memory rates A novel methodology was employed, in which words from the Deese-Roediger-McDermott (DRM) paradigm word list were used to craft narrative stories, with critical lures left out of the narratives. Participants performed a recognition task at the end of each narrative read to test for false memory susceptibility. Emotional framing at encoding was hypothesized to increase false memory rates compared to perceptual framing, and higher emotional intensity was predicted to lead to greater false memory rates. Results were consistent with prediction for encoding contexts, but not for emotional intensity.